Absence of Nkx2-3 induces ectopic lymphatic endothelial differentiation associated with impaired extramedullary stress hematopoiesis in the spleen - Gábris, Fanni; Kiss, Gabriella; Szirmay, Balázs; Szomor, Árpád; Berta, Gergely; Jakus, Zoltán; Kellermayer, Zoltán; Balogh, Péter (Frontiers in Cell and Developmental Biology, 2023)
The red and white pulps as two main parts of the spleen are arranged around distinct types of vasculature, and perform significantly different functions in both humans and mice. Previous observations indicated a profound alteration of the local vessel specialization in mice lacking Nkx2-3 homeodomain transcription factor, including contradictory results suggesting presence of an ectopic lymphatic vascular structure. Furthermore, how the absence of Nkx2-3 and the consequential changes in endothelial components affect the extramedullary hematopoietic activity restricted to the splenic red pulp is unknown. In this work, we investigated the role of Nkx2-3 homeodomain transcription factor as a major morphogenic determinant for vascular specification, and its effect in the extramedullary hematopoiesis following acute blood loss and pharmacological stimulation of megakaryocyte differentiation after treatment with thrombopoietin-receptor mimetic Romiplostim. We found that, in mice lacking Nkx2-3, Prox1-positive lymphatic capillaries containing gp38/CD31 double positive lymphatic endothelial cells develop, arranged into an extensive meshwork, while the Clever1-positive venous segments of red pulp blood vasculature are absent. This lymphatic endothelial shift is coupled with a severely compromised splenic erythropoiesis and a significantly reduced splenic megakaryocyte colony formation following Romiplostim treatment in mice lacking Nkx2-3. These findings indicate that the shift of microvascular patterning in the absence of Nkx2-3 includes the emergence of ectopic Prox1-positive lymphatic vessels, and that this pivoting towards lymph node-like vascular patterning is associated with an impaired reserve hematopoietic capacity of the splenic red pulp.